Ox-eye windows with stained glass decoration - Ghosh, Ayan (Jio Institute, 2023)
Frederick Stevens’ design of large windows allowed plenty of natural light and breeze to pass through, keeping the buildings ventilated and illuminated. This was a practical necessity because at the time of its construction, buildings didn't have electricity. The BMC building was, in fact, the first building in Mumbai to be fully electrified before inauguration.